2019
DOI: 10.1145/3335081
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Motivations of Crowdworkers

Abstract: Crowd employment is a new form of short-term and flexible employment that has emerged during the past decade. To understand this new form of employment, it is crucial to illuminate the underlying motivations of the workforce involved in it. This article introduces the Multidimensional Crowdworker Motivation Scale (MCMS), a scale for measuring the motivation of crowdworkers on microtask platforms. The MCMS is theoretically grounded in self-determination theory and tailored specifically to the context of paid cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…To bolster the crowdworkers' motivation, reward setting is one of the most important issues (Posch et al, 2019). In this paper, we tested two types of rewards: fixed or variable.…”
Section: Reward Settingsmentioning
confidence: 99%
“…To bolster the crowdworkers' motivation, reward setting is one of the most important issues (Posch et al, 2019). In this paper, we tested two types of rewards: fixed or variable.…”
Section: Reward Settingsmentioning
confidence: 99%
“…The results of the three approaches also provided evidence for convergent validity (i.e., if the items converge and have a high proportion of variance in common). Posch et al (2019) indicated that significant factor loadings and an AVE less than CR is evidence of convergent validity. For the three subscales, all of the factor loadings were significant, and, in all instances, AVE < CR.…”
Section: Discussionmentioning
confidence: 99%
“…Convergent validity of the VAX was demonstrated through significant factor loadings [ 45 , 46 ], AVE > 0.50, and AVE < CR [ 46 ]. The latter indices indicated that the variance explained by the scale (or subscales) is greater than cross-loadings or measurement error [ 47 ].…”
Section: Discussionmentioning
confidence: 99%